The Use of Memrise NGSL 1.01 Flashcard Set Apps to Learn General Vocabulary in The Tenth Grade of Senior High School 1 Praya Timur - Hidayatullah, Muhammad Isro'; Melani, Boniesta Zulandha; Lail, Husnul; Apgrianto, Kurniawan (Journal of Classroom Action Research, 2024)
This study aims to explore the impact of using the Memrise mobile app, specifically its New General Service List (NGSL) 1.01 flashcard sets, on English vocabulary acquisition among high school students. Recognizing vocabulary as a critical component of language mastery, this research addresses the challenges in vocabulary learning and the potential benefits of digital tools in enhancing language skills. This study employs a pre-experimental with one-group pre-test–post-test design. the study involved 35 tenth-grade students from Senior High School 1 Praya Timur. Then, the NGSL diagnostic test (NGSL vocabulary test with multiple choice form) was used to measure vocabulary knowledge before and after a five-week intervention with the Memrise app. The results of this study indicated significant improvements in vocabulary scores post-intervention, demonstrating the app's effectiveness. A positive correlation was found between the number of flashcard sets used and students' NGSLT scores. The findings suggest that digital learning platforms like Memrise can significantly enhance vocabulary acquisition, making learning more engaging and effective. The study recommends integrating such tools into educational practices to improve vocabulary learning outcomes. Future research should investigate the long-term effects and demographic variations in the effectiveness of digital vocabulary learning tools.